The effect of Sleep Leadership Training on U.S. Army human performance team members - Barrow, Talia; Yu, Bryan; Cooper, Carly; DaLomba, Elaina; Gregg, Brian; Barefield, Maria; Umlauf, Jon (Frontiers in Sleep, 2024)
Most U.S. Servicemembers (SMs) get less than the recommended amount of sleep per night, which has been shown to be directly influenced by local leadership. Previous research demonstrated that a brief sleep leadership training (SLT) protocol resulted in improved knowledge and attitudes regarding sleep among U.S. Army leaders, and improvements in the sleep health of their SMs. Human Performance Teams (HPT) offer one solution to propel the cultural change related to sleep, however, little is known about HPT members' own sleep related knowledge, practices, attitudes, and beliefs. This mixed-methods study determined the effect of (SLT) on the sleep-related knowledge, practices, attitudes, beliefs, and perceived competency of HPT members, explored their experiences addressing SM sleep, and gauged their perceived value in receiving the training. Thirty-one individuals received two days of SLT. Baseline and 6-week post training follow-up measures were collected, and participants were invited to participate in semi-structured interviews to explore their unique experiences addressing sleep, as well as their perceived value in receiving SLT. Training had no significant effects on HPT members' sleep practices or sleep beliefs, some significant effects on their attitudes and knowledge about sleep, and significant effects on their perceived competence to address sleep in their units. Results suggest that HPT members benefited from the training through enhancement of their competence to address sleep with leadership. However, they struggle to obtain sufficient sleep themselves. More research is needed to identify methods of overcoming specific barriers to sleep imposed on SMs.